PENGELOLAAN WADUK BAGI KELESTARIAN DAN KEANEKARAGAMAN HAYATI IKAN - Jubaedah, Iis (Politeknik Pembangunan Pertanian Bogor, 2006)
Reservoir is an open water ecosystem that built in the river system. The development ofreservoir will change lotic ecosystem to lentic ecosystem. The species of fishies should beadapted to the reservoir which is needed a high tolerance to water quality and fish foodchanges at every habitat.The distribution of fish in reservoir depends on abiotic and biotic factor, such as:morphohidrodinamic, light, temperatur, flow velocity, pH and dissolved oxygen and bioticfactor, such as: natural foods, predation, competition and human being.Form biological aspect point of view, composed of too aims. The purpose of fisheriesresources management. The first, is to protect the fish stock by avoiding over fishing and thesecond, is to conserve indigenious fish spesies in order to have a balance ecosystem.